(untitled) (Global Journal of Management and Business Research, 2019)
The concept of marketing communication strategies assumes that there are several variables which will help to influence donors as well as receivers to accomplish the nonprofit organization’s goal. Based on the marketing communications and business-to-business marketing literature, the model -integrates aspects of the marketing communication purposes, bidirectional communications, and different communications channels-is experienced to examine marketing communication strategies and organizational performance in terms of nonprofit organizations. The purpose of the paper is to identify and analyze promotional strategies taken by NGO’s working in Bangladesh and find out lacking in terms of strategies and by understanding consumer’s perception; providing suggestions regarding creating policies in the perspective of attracting both donor and receiver. However, this study uses an exploratory case methodology where both primary and secondary data were used for analyzing the applied and applicable strategies. For Primary data collection, 10 NGOs were chosen which are working in Bangladesh and in-depth interview was taken from high officials.